2006
DOI: 10.1158/0008-5472.can-06-1333
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nongenomic Activation of Phosphatidylinositol 3-Kinase/Akt and Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase Kinase/Extracellular Signal-Regulated Kinase 1/2 Pathways in 1,25D3-Mediated Apoptosis in Squamous Cell Carcinoma Cells

Abstract: Vitamin D is a steroid hormone that regulates calcium homeostasis and bone metabolism. The active form of vitamin D [1A,25-dihydroxyvitamin D 3 (1,25D3)] acts through both genomic and nongenomic pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…14,15 Little or no apoptosis is induced by 1,25D 3 in SCC cells when the entire population is assessed. 14,16 In the fraction of floating SCC cells following 1,25D 3 treatment, apoptosis can be detected, 17 suggesting that the floating cells account for a small part of the whole population. The ability of inecalcitol to induce apoptosis appears to be cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Little or no apoptosis is induced by 1,25D 3 in SCC cells when the entire population is assessed. 14,16 In the fraction of floating SCC cells following 1,25D 3 treatment, apoptosis can be detected, 17 suggesting that the floating cells account for a small part of the whole population. The ability of inecalcitol to induce apoptosis appears to be cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…SCC and SCC-DR cells were collected and stained with PE-conjugated annexin V and 7AAD, according to manufacturer's instructions, as described previously. 16 Caspase activity assays. The activities of caspases-3, 8, 9 (R&D Systems) and caspase 10 (EMD Millipore) were measured using the caspase fluorometric assay kit following the manufacturer's protocols.…”
mentioning
confidence: 99%
“…The pro-apoptotic effect of wogonin was found to be mediated via activation of ERKs and caspases and is correlated with interruption of the PI3K/Akt/survivin signaling pathways in MCF-7 cells (20). A number of studies have shown the importance of ERK signaling in the regulation of apoptosis (26,27). Although the ERK pathway delivers a survival signal, studies using chemopreventive and chemotherapeutic agents have linked activation of ERKs with induction of apoptosis (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stained with Annexin V-PE and 7-AAD according to the manufacturer's instructions (BD Pharmingen). 14 The data was analysed using Winlist TM program (Verity House, Topsham, ME).…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Calcitriol has also been shown to reduce angiogenesis in a number of cancer models, which also contributes to the antitumor effect of calcitriol in vivo. 2 …”
Section: Introductionmentioning
confidence: 99%